Intensification of Personality Competence and Professionalism of PAI Teachers In The Lessoning Process - Handayani, Laily Rachma; Ghufron, David Maulana; Kunaepi, Aang (IAIN Ponorogo, 2023)
This research was conducted with the aim of knowing in depth about the personality competence and professional competence that a teacher must have. In addition, this study also discusses how efforts can be made to improve the professionalism and personality of teachers in order to support the learning process well so that it can achieve the learning objectives desired by the school/madrasa. This research is a qualitative research with a data collection process through literature study. The data analysis process in this study adopted from Miles and Hubermen. While data validity uses triangulation techniques. The results showed that the essence of a PAI teacher is how a teacher can lead his students to become a caliph on earth as well as a servant of Allah through a learning process that is in accordance with Islamic law. To be able to achieve this, a teacher needs to equip himself with various competencies, one of which is personality competence and professional competence. Personality competence must be owned by the teacher because it is the teacher who must be a role model and a good example for his students. While professional competence is needed so that a teacher can manage and organise the class and can convey knowledge effectively and efficiently. So that in order to achieve these competencies, teachers are required to attend training and upgrading that can improve the quality of teacher performance.